Double‐balloon enteroscopy for choledochojejunal anastomotic stenosis after hepato‐biliary‐pancreatic operation. Issue 1 (3rd November 2014) - Sakakihara, Ichiro; Kato, Hironari; Muro, Shinichiro; Noma, Yasuhiro; Yamamoto, Naoki; Harada, Ryo; Horiguchi, Shigeru; Tsutsumi, Koichiro; Okada, Hiroyuki; Yamamoto, Kazuhide; Sadamori, Hiroshi; Yagi, Takahito
<x xml:space="preserve">Abstract</x> Background and Aim There have been few reports on the success rate of balloon dilation and stent deployment using endoscopic retrograde cholangiopancreatography by double‐balloon enteroscopy (DBE‐ERCP) or on the follow‐up period after stent removal in patients with a reconstructed digestive tract and stenosis of choledochojejunal anastomosis. The present study was designed to evaluate the usefulness of DBE‐ERCP in patients with a reconstructed digestive tract and stenosis of choledochojejunal anastomosis. Methods Forty‐four patients with stenosis of choledochojejunal anastomosis underwent DBE‐ERCP at Okayama University Hospital between April 2008 and January 2012 (107 procedures). Rates of reaching choledochojejunal anastomosis, stent deployment, and restenosis after stent removal were retrospectively evaluated. Results Insertion of DBE into the choledochojejunal anastomotic site succeeded in 38 of 44 patients (86.4%), and anastomotic dilation and stent deployment succeeded in 36 of 44 patients (81.8%). In 32 of 44 patients (72.7%), their anastomotic stenoses were improved, and they achieved stent removal. After stent removal, restenosis of choledochojejunal anastomosis was detected in seven of 32 patients; however, the resolution of restenosis was achieved in all seven of those patients. Conclusion Dilation of choledochojejunal anastomosis combined with stent deployment using DBE‐ERCP seems to be a viable first‐line treatment for patients with stenosis of choledochojejunal anastomosis.